Experimental verification of the data processing algorithms for GPR testing of pavements - Батракова, А. Г. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 2017)
The paper discusses the results of experimental verification of the previously proposed data processing algorithms for GPR survey of roads and the evaluation of the reproducibility of the measurement results. On the basis of preliminary experimental studies confirmed the reproducibility of the temporal delay measurement signal during the passage of the probe pulse through the test construction of pavement on Cochran's criterion for significance level of 0,95. Experimentally confirmed availability and adequacy of the developed models and algorithms based on the receipt and processing of the calibration signals of GPR in solving the problem of determining the dielectric constant and thickness of the structural layers of road pavements of non-rigid type